Search for a charged Higgs boson decaying to charm and bottom quarks in proton-proton collisions at s√=8s=8 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2018, 2018)
Title screen